Breves apuntes respecto de la “nulidad manifiesta” como presupuesto material de su “apreciabilidad” de oficio en el ordenamiento jurídico peruano - Campos García, Héctor Augusto (2016)
One of the main objectives of any legal system is legal certainty, which is understood as the provision of decisions in the work of the courts. To this end, in order to standardize the diversity of decisions of courts for the same conflict, there are meetings of supreme judges who seek to give a unique sense of resolution to the same conflict. Those meetings are called Cassation Plenaries.In this article, the author comments and develops the decision taken at the IX Civil Cassation Plenary. At that meeting a broad criterion of manifested nullity has been chosen, whenever the causal is “easy to warn”. However, throughout the text the author highlights the methodological vices of the Supreme Court to reach this conclusion and, using a legal comparison, proposes a different criterion of manifest nullity, demonstrating that for our legal system this should not be restricted to an “easy to warn” causation.